Girly mags and girly jobs: Pornography and gendered inequality in forensic practice. (17th September 2012) - Mercer, Dave
Abstract This article presents findings from a discourse analytic study into the constructive nature and textual variations of language in a high‐security hospital. It explores how mental health nurses, and men convicted of sexual offences who also have a diagnosis of personality disorder, talked about pornography and sexual crime in the context of forensic provision. Access to sexually‐explicit media, in relation to treatment environments for people convicted of sexual offences, has become a cause for professional and political concern in the UK. Data collection and analysis, undertaken concurrently, were informed by a discursive design. Semistructured interviews, as co‐constructed accounts with nursing staff and detained patients, were audio‐taped and transcribed. Data were coded to identify the discursive repertoires, or collective talk, of respondents. In contrast to empirical inquiry into pornography and sexual violence, methodology shifted attention from measurement to meaning, and situated research in a clinical domain. The findings focus on performative language use, where talk about pornography textured the treatment environment, contributed to an overtly masculine discourse, framed the ward as male space, and promoted gendered inequality. The discussion questions the legitimacy of the therapeutic enterprise.